SP0073 Molecular Control of Cell Fate Determination in Cartilage and Joint Development. (10th June 2014) - Lefebvre, V.
Abstract : The healthy development and adult maintenance of the various structures that make up our skeleton rely on tight coordination of multiple events. These events include cell fate decisions made by multipotent mesenchymal progenitor/stem cells and differentiated cell types to either survive or die, proliferate or growth arrest, migrate or settle, and maintain stemness or differentiate. These decisions are controlled by both cell-autonomous and non-cell-autonomous mechanisms, i.e., mechanisms dependent on intrinsic properties of cells and on external cues, respectively. A pivotal decision made by every mesenchymal cell of the onset of skeletogenesis is to be or not to be a chondrocyte. Sox9 forms with its functional partners, Sox5 and Sox6, a trio of transcription factors required cell-autonomously for the commitment and differentiation of mesenchymal cells into chondrocytes. In contrast, beta-catenin is a structural protein and transcriptional co-activator required to divert cells from the chondrocyte lineage and secure their differentiation into non-chondrocytic cell types. These cell types include prospective articular joint cells. Antagonism between Sox9 and beta-catenin thus governs the proper design, development and articulation of all cartilage templates of future bones. Although it acts cell-autonomously, beta-catenin is critically dependent upon canonical Wnt signaling to be stable and thus capable of achieving its functions. This pathway acts for a large part non-cell-autonomously. As of today, it remains unknown whether articular progenitor cells and other non-chondrocytic cell types use cell-autonomous mechanisms to stabilize beta-catenin and thereby secure their lineage fate. We will show here that we have newly identified a distinct trio of Sox proteins that has this unique property. This trio is composed of Sox4, Sox11, and Sox12, the three members of the SoxC group. Their inactivation in multipotent mesenchymal progenitors in the mouse embryo results in a severe skeletal dysplasia. Cartilage primordia form, but remain tiny and are fused with each other due to a total absence of articular joints. The SoxC genes are actively expressed in mesenchymal progenitor cells, including presumptive joint cells. They have a key role in stabilizing beta-catenin and thereby in repressing Sox9 expression and securing the non-chondrocytic fate of the cells. Thus, the SoxC non-chondrocytic trio and the Sox5/6/9 chondrogenic trio have opposite actions that are both necessary to decide the fate of mesenchymal progenitor/stem cells and thereby develop a harmonious and fully functional skeleton, including articular joints. Future studies are necessary to determine whether and how these two Sox trios continue to direct and secure cell fate in adult joints under healthy and rheumatic conditions. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.6330